Students’ Perception of The Use of Mind Mapping as a Visual Learning Tool - Sentyawati, Kadek Anggun (English Education Department STKIP Agama Hindu Singaraja, 2022)
Senior high school is the grade where young learners face the most complex lesson. The complex lesson leads students to have learning tools that could help them in the learning process. Mind mapping is one of creative visual learning tool that make the lesson becomes clearer. This study is aim to find the students’ perception of the use of mind mapping as visual learning tool at SMA Negeri 1 Singaraja. The study used qualitative research method design. The data of this study were collected by open-ended questionnaire and interview. The subjects of this study were 16 students of twelve grade students of SMA N 1 Singaraja which selected randomly. The result of the study showed that the students have positive perception towards the use of mind mapping as a visual learning tool. The majority of the students agreed that mind mapping can really help them in making summary and taking notes, giving them opportunity to be more creative, and helping them in developing their ideas.